2005
DOI: 10.1200/jco.2004.00.8151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Hormone Replacement Therapy on Breast Cancer Risk Reduction After Bilateral Prophylactic Oophorectomy in BRCA1 and BRCA2 Mutation Carriers: The PROSE Study Group

Abstract: Short-term HRT use does not negate the protective effect of BPO on subsequent breast cancer risk in BRCA1/2 mutation carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
224
0
23

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 384 publications
(247 citation statements)
references
References 27 publications
0
224
0
23
Order By: Relevance
“…In the only study published to date, Rebbeck et al (2005) reported that the protective effect offered by oophorectomy was not attenuated by the prescription of HRT. Compared to women who did not have an oophorectomy, the combination of HRT and oophorectomy was associated with a significant reduction in breast cancer risk (hazard ratio ¼ 0.37, 95% CI: 0.14-0.96).…”
Section: Hormone Replacement Therapymentioning
confidence: 98%
“…In the only study published to date, Rebbeck et al (2005) reported that the protective effect offered by oophorectomy was not attenuated by the prescription of HRT. Compared to women who did not have an oophorectomy, the combination of HRT and oophorectomy was associated with a significant reduction in breast cancer risk (hazard ratio ¼ 0.37, 95% CI: 0.14-0.96).…”
Section: Hormone Replacement Therapymentioning
confidence: 98%
“…Low-dose hormone replacement therapy (HRT) does not appear to decrease the preventive effect of SO on the BC risk. 44 In women younger than 50 years of age with no history of BC, HRT may be prescribed 45 in the presence of severe menopausal symptoms. The age at which SO should be recommended is still a subject of controversy, particularly in BRCA2 carriers.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the mortality of ovarian cancer, BRCA1/2 mutation carriers are currently being counselled for gynaecological screening and prophylactic bilateral (salpingo-) oophorectomy (BP(S)O). Although efficacy of BPSO has been demonstrated (Rebbeck et al, 2005), the efficacy of gynaecological screening with (bi) annual transvaginal ultrasonography (TVU) and the serum tumour marker CA125 (Karlan et al, 1993;Burke et al, 1997) is still unclear. To summarize the literature on gynaecological screening of BRCA1/2 carriers, including overlap with the present study, eight interval cancers among 24 cancers were diagnosed among a total of 807 BRCA1/2 carriers (Table 1) (Laframboise et al, 2002;Liede et al, 2002;Scheuer et al, 2002;Fries et al, 2004;Kauff et al, 2005;Meeuwissen et al, 2005;Vasen et al, 2005;Gaarenstroom et al, 2006;Oei et al, 2006).…”
mentioning
confidence: 99%